Does cancer of unknown primary (CUP) truly exist as a distinct cancer entity? - Bochtler, Tilmann; Krämer, Alwin (Frontiers in oncology, 2019)
Cancer of unknown primary (CUP) designates an enigmatic cancer entity with histologic confirmation of malignancy from a metastasis but no identifiable primary tumor in spite of a thorough diagnostic work-up. In this review, we discuss the validity of CUP as a distinct cancer entity as well as diagnostic pitfalls. As arguments against a distinct entity, the diagnosis of CUP is erroneous in some cases. Diagnostic pitfalls include incomplete diagnostics, uncertainty in classifying a lesion as either primary or metastasis and mistaking a relapse of an antecedent malignancy as CUP due to histologic and immunohistologic disparities. Given the high frequency of prior malignancies in CUP patients, relapse of an antecedent cancer should always be carefully excluded. Gene expression profiling-based classifier assays aim at aligning the molecular profile of CUP patients with established primary cancer patterns for highest congruency in order to identify the putative primary and treat accordingly. However, the spectrum of predicted putative primaries by molecular techniques is somewhat at odds with the primaries identified in autopsy series. Also, a first randomized clinical trial did not show superiority of primary-tailored therapy over unspecific platinum-based chemotherapy. CUP syndromes share an aggressive clinical course, atypical metastasis pattern, rapid progression of metastases, a generally poor response to chemotherapy and dismal outcome as distinct clinical features. Metastatic spread appears to take place in the early stages of tumor evolution, with CUP metastases subsequently undergoing genetic evolution towards a chromosomally highly complex and instable karyotype independent from the primary tumor. In clinical practice, the diagnosis of CUP is valid when no primary tumor is detectable. Treatment should ideally offer broad spectrum coverage across numerous malignancies and be well established in CUP as is the case for carboplatin / paclitaxel and cisplatin / gemcitabine in particular, but it should also cover the most likely putative primary. The diligent diagnosis of CUP is warranted for clinical trials, making the eligibility process particularly laborious. In conclusion, we affirm CUP as a distinct cancer entity and the validity of the diagnosis in most patient cases.
Gesehen am 24.06.2019